Optimal placement of wind generation units in order to increase revenues and reduce the imposed costs in the distribution system considering uncertainty - Seyed Mohsen Mousavi Khormandichali; Mehrdad Ahmadi Kamarposhti (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Recent advances in the field of new energies such as wind turbines, solar power plants, fuel cells, micro-turbines, etc., and also the great benefits of these power plants for the power network, attract the attention of distribution companies towards them. As, today, many distribution companies are examining options for changing the distribution network structure in order to exploit new energies. In the meantime, wind energy is one of the most widely used types of distributed generation in the power network. In addition, wind power generation has the most changes to other types of renewable energy. Distribution network planning is one of the major concerns of system designers, especially when wind generation units by their random and variable nature are in system development. Since the proper placement of wind units in the network plays an essential role in improving the performance of the distribution network, providing a comprehensive and appropriate solution for placement of these units in the network is important. In this paper, a method has been presented that by considering the uncertainty in generation and consumption and the network constraints, the placement of wind units in the network is done with the aim of increasing revenues and reducing the imposed costs in the distribution system, taking into account the uncertainity. The algorithm used in this paper is a genetic algorithm with improved operators.